2015
DOI: 10.1016/j.trf.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

The bicycle and the dream of a sustainable city: An explorative comparison of the image of bicycles in the mass-media and the general public

Abstract: This paper explores the representation of the bicycle by comparing data from various mass media sources and the general public in Italy. In study 1, a number of commercial advertisements published on paper magazines and aired by the major TV channels, as well as 405 articles published by the major online newspapers were content analysed in order to identify the main concepts and evaluations characterising the representation of bikes in the media. In study 2, 94 Rome residents were interviewed on their beliefs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
(20 reference statements)
1
13
0
Order By: Relevance
“…This study addresses the question, drawing on social representation theory (SRT) as an overarching framework (Sammut et al 2015;Wagner et al 1999), and extending previous studies conducted in Italy (Passafaro et al 2014;Rimano et al 2015;Sarrica et al 2019) on social representations (SRs) of cycling. In particular, by acknowledging the emphasis that SRT places on societal transformations and communication, we examine whether ebikes have brought about a relevant shift in the SRs of bicycles and cycling conveyed by the press.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…This study addresses the question, drawing on social representation theory (SRT) as an overarching framework (Sammut et al 2015;Wagner et al 1999), and extending previous studies conducted in Italy (Passafaro et al 2014;Rimano et al 2015;Sarrica et al 2019) on social representations (SRs) of cycling. In particular, by acknowledging the emphasis that SRT places on societal transformations and communication, we examine whether ebikes have brought about a relevant shift in the SRs of bicycles and cycling conveyed by the press.…”
Section: Introductionmentioning
confidence: 86%
“…Cycling was either for leisure or considered as a means of transport for low-income groups. Research in Italy on the SRs shared by the media and the country's residents showed that the bicycle embodied the dream of sustainable cities of the future rather than a concrete solution to present-day urban problems (Rimano et al 2015). Further studies confirmed that bicycles are still regarded as belonging not to the here and now, but to another place and time, and especially by people with no personal experience of cycling (Sarrica et al 2019).…”
Section: Cultural and Symbolic Factorsmentioning
confidence: 98%
“…Another research was studied in Beijing, where the increasing city size and urban expansion were great challenges to cycling systems [3]. The sustainable awareness from various mass media sources and the general public was studied in Italy and found that some respondents overlap in perceiving of using bike in the city [4]. Although, the sustainable awareness of using bicycle had similar in several cities, there is still need to be further studied in society perceiving of sustainable paper bicycle.…”
Section: Introductionmentioning
confidence: 99%
“…), social media and different user-groups (particularly university students) as enablers is discussed in various articles (e.g. Rose & Marfurt, 2007;Rimano et al, 2015;Gozun & Guillen, 2008).…”
Section: Literature On Development Of Cycling As a Transport Modementioning
confidence: 99%
“…The public discourse is analysed using printed and social media published between 2013 and 2015 for Thailand (40 articles 42 ) and the Philippines (20 articles 1 ) respectively, following e.g. Gössling (2013), who carried out a similar content and discourse analysis for Copenhagen, and Rimano et al (2015), who investigate the mass media image of bicycles by performing a cluster analysis on 'risk and danger', 'sustainable mobility', 'wellness and leisure' for Italy.…”
Section: Analysis Framework: Technological Innovation Systemsmentioning
confidence: 99%